ECOLOGICAL ASSESSMENT OF POPULATION HEALTH INDICATORS IN THE REPUBLIC OF KARAKAPAKSTAN AND THEIR RELATIONSHIP WITH THE ENVIRONMENT - М.К. Tadjibaeva; S.М Mambetullaeva (The journal of contemporary issues in business and government, 2021)
The article presents the study results, the ecological assessment of population health indicators of the Republic of Karakalpakstan and their relationship with the environment.The structure analysis of the nosological disease forms distribution showed that there is some redistribution of the main nosologies.The environment acts as a whole, and the whole influence is always greater than the sum effect of the individual parts.